Antimicrobial Susceptibility Profile of Several Bacteria Species Identified in the Peritoneal Exudate of Cows Affected by Parietal Fibrinous Peritonitis after Caesarean Section - Salem Djebala; Julien Evrard; Fabien Gregoire; Calixte Bayrou; Linde Gille; Justine Eppe; Hélène Casalta; Vincent Frisée; Nassim Moula; Arnaud Sartelet; Damien Thiry; Philippe Bossaert (Veterinary Sciences, 2021)
The aim of this study was to identify the species and antimicrobial susceptibility of bacteria involved in parietal fibrinous peritonitis (PFP). We studied 156 peritoneal fluid samples from cows presenting PFP after caesarean section. Bacteria were cultured in selective media and their antimicrobial susceptibility was tested by disk diffusion assay. Bacteria were isolated in the majority (129/156; 83%) of samples. The majority (82/129; 63%) of positive samples contained one dominant species, while two or more species were cultured in 47/129 (36%) samples. Trueperella pyogenes (T. Pyogenes) (107 strains) was the most identified species, followed by Escherichia coli (E. coli) (38 strains), Proteus mirabilis (P. mirabilis) (6 strains), and Clostridium perfringens (C. perfringens) (6 strains). Several other species were sporadically identified. Antimicrobial susceptibility was tested in 59/185 strains, predominantly E. coli (38 strains) and P. mirabilis (6 strains). Antibiotic resistance, including resistance to molecules of critical importance, was commonly observed; strains were classified as weakly drug resistant (22/59; 37%), multidrug resistant (24/59; 41%), extensively drug resistant (12/59; 20%), or pan-drug resistant (1/59; 2%). In conclusion, extensive antibiotic resistance in the isolated germs might contribute to treatment failure. Ideally, antimicrobial therapy of PFP should be based upon bacterial culture and susceptibility testing.